4D printing of shape-changing structures based on IPN epoxy composites formed by UV post-curing and γ-ray radiation. (November 2022) - Wang, Linlin; Zhang, Fenghua; Du, Shanyi; Leng, Jinsong
Graphical abstract: Abstract: The cross-linking degree is a significant factor affecting the thermodynamic properties of resins, the cross-linking degree of photosensitive resins is limited during Digital Light Procession (DLP) printing. We present a strategy for double networks in epoxy resin to further improve the performances of printed structures via two different processing methods. Epoxy acrylates and polyethylene glycol dimethacrylates crosslink by UV-light radiation forming a light-induced network structure, and epoxy molecules crosslink under γ-ray radiation forming a ray-induced network structure. The two kinds of networks interpenetrate to form the interpenetrating polymer network (IPN). The printed IPN specimens have the characteristics of high Young's modulus (up to 4.89 GPa) and fracture strain (as high as 30.4 %). The printed flowers and canister reinforced by short glass fibers (GFs) exhibited rapid shape recovery behaviors. The IPN epoxy/GFs composites have good values in manufacturing smart deployable structures, medical devices, and automobile shell parts.